STRATEGI PSIKOANALISIS GURU BIMBINGAN KONSELINNG DALAM MENANGANI KENAKALAN SISWA DI SMA N 1 BATUR BANJARNEGARA - Aji Bayu Prabowo; Rifqi Muntaqo; Salis Irvan Fuadi (Universitas Maritim AMNI Semarang, 2022)
The title of the counseling guidance teacher's efforts in dealing with delinquency in class XI students at SMA N 1 Batur, Batur District, Banjarnegara Regency, in this study has an educational background that is closely related to a strong character. Meanwhile, development in Indonesia is carried out as a whole, which requires quality human resources, various efforts for the formation of the nation's personality, especially in the younger generation. One of the efforts to improve quality resources is through education. However, every educational process, especially tackling delinquency, has an obstacle and obstacle, which occurs in SMA N 1 Batur, especially class XI, from this research it has a goal. 1) knowing the efforts of BK teachers in dealing with student delinquency; 2) knowing the method used; 3) knowing the inhibiting and supporting factors, by using qualitative methods that produce descriptive data, then data collection techniques through interview observations and documentation, in analyzing data systematically, organizing data, describing data into units and compiling into a pattern that produces a conclusion, namely learning that occurs at SMA N 1 Batur is in accordance with the objectives and procedures for learning, then in each lesson several factors, both supporting and inhibiting factors, are found from internal and external sources, and several efforts have been made by counseling teachers at SMA N 1 Batur Banjarnegara..